Feedback design of differential equations of reconstruction for second-order distributed parameter systems - Maksimov, Vyacheslav I.; Mordukhovich, Boris S. (Zielona Góra: Uniwersytet Zielonogórski)
The paper aims at studying a class of second-order partial differential equations subject to uncertainty involving unknown inputs for which no probabilistic information is available. Developing an approach of feedback control with a model, we derive an efficient reconstruction procedure and thereby design differential equations of reconstruction. A characteristic feature of the obtained equations is that their inputs formed by the feedback control principle constructively approximate unknown inputs of the given second-order distributed parameter system.
Keywords: second-order partial differential equation; equations of reconstruction